Pengaruh Fasilitas Perpustakaan terhadap Minat Membaca Peserta Didik Kelas IX Pesantren Modern Tarbiyah Takalar - Hasanuddin, Hannur Jannah; Ruhaya, Besse; Latuconsina, Nur Khalisah; Salahuddin; Munawwir, Ahmad (Faculty of Tarbiyah and Teacher Training, 2024)
This research aims to determine the influence of library facilities on the reading interest of class XI students at the Tarbiyah Takalar Modern Islamic Boarding School. This research is quantitative research using an ex post facto method. The respondents in this research were class XI students at the Tarbiyah Takalar Modern Islamic Boarding School. Data collection in this research used a questionnaire instrument consisting of 20 statements, which were then analyzed using descriptive statistics and linearity analysis. Based on the results of descriptive statistical analysis, it can be concluded that the Tarbiyah Takalar Modern Islamic Boarding School's library facilities are in the medium category with a percentage of 72.2%, while the reading interest of class XI students at the Tarbiyah Takalar Modern Islamic Boarding School is also in the medium category with a percentage of 69.4%. This research also showed an influence between library facilities and the reading interest of class XI students at the Tarbiyah Takalar Modern Islamic Boarding School.